1977
DOI: 10.2135/cropsci1977.0011183x001700010013x
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Winter‐type Selections of Safflower1

Abstract: Plants with a long‐rosette period were identified in one of the local populations of safflower (Carthamus tinctorius L.) from northwestern Iran. Fifty‐one lines developed from these plants showed considerable variation in winter hardiness, seed yield, oil content, oil yield per hectare, number of heads per plant, and 1,000‐seed weight. The superior winterhardiness of rosette (winter) types over non‐rosette (spring) types should permit fall seeding of safflower in areas where winter temperatures go as low as −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…In many respects our results were quite diff erent than previous research on winter-type saffl ower conducted by Ghanavati and Knowles (1977) and Yazdi-Samadi and Zali (1979) in Iran. Their winter types had a long rosette period, as long as 120 d, and apparently required a cold period at the rosette stage for maximum seed production (Ghanavati and Knowles, 1977). We defi ned winter types as those with a capacity for winter survival; the rosette period or a cold requirement for reproduction development were not directly considered.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In many respects our results were quite diff erent than previous research on winter-type saffl ower conducted by Ghanavati and Knowles (1977) and Yazdi-Samadi and Zali (1979) in Iran. Their winter types had a long rosette period, as long as 120 d, and apparently required a cold period at the rosette stage for maximum seed production (Ghanavati and Knowles, 1977). We defi ned winter types as those with a capacity for winter survival; the rosette period or a cold requirement for reproduction development were not directly considered.…”
Section: Discussioncontrasting
confidence: 99%
“…During the rosette stage saffl ower is relatively cold tolerant (Yazdi-Samadi and Zali, 1979). As a result, winter survival has been associated with a long rosette period (Yazdi-Samadi and Zali, 1979), and genotypes with a prolonged rosette period usually have increased cold tolerance and are considered winter types (Ghanavati and Knowles, 1977). Yet a clear distinction between rosette and non-rosette habit can be arbitrary and is infl uenced by genotype and environmental conditions and heritable genetic traits (Zimmerman, 1976;Zimmerman and Buck, 1977).…”
mentioning
confidence: 99%
“…However, any cold tolerance they possess was insufficient for the winter conditions observed in the current study. Winter types of safflower, which have the capability to withstand temperatures substantially lower than can spring types, have a longer rosette period (Ghanavati and Knowles 1977;Yazdi-Samadi and Zali 1979). Passport data from the Germplasm Resources Information System (GRIN) state that KN-144 is a winter type from Iran (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of this stage is not only dependent on environment but on heritable genetic traits (Zimmerman 1976;Zimmerman and Buck 1977). Ghanavati and Knowles (1977) found high cold tolerance in plants with a long rosette period collected from northwest Iran. Li et al (1997) also found safflower with a prolonged rosette habit in China.…”
Section: Mots Clésmentioning
confidence: 94%
See 1 more Smart Citation